DEPICT THE ROLE OF FACTORS AFFECTING BEHAVIOR OF INVESTORS TOWARD SETTING THE INVESTMENT AVENUES AND CHOOSING THE BEST INVESTMENT PLATFORM: AN EMPIRICAL ANALYSIS - Sharma, Suraj; Tripathi, Ashish (Indian Journal of Finance and Banking, 2022)
The present study depicts the role of various factors affecting the behavior of investors towards set investment platforms and their priorities in choosing the best investment avenues. Its first aim is to get fully acquainted with various factors: Demographics and other influencing factors affecting investors' behavior towards choosing investment avenues. The second aim is to find the best investment platform in the Indian financial system. The third one perceives investors' perceptions and behavior while choosing their best investment priority and selecting the best investment platform. And fourth measures the relationship between various factors and investment avenues. The study mainly concerns and focuses on generating new epistemology (knowledge) in financial investment decisions with the effect of influencing factors for choosing the best investments, simultaneously getting a conceptual framework with Financial Behavior & Attitude glimpse. This study hypothesizes the demographic factors affecting behavior or not and measures relationships between other investment influencing factors & investment avenues. The study has conducted an empirical analysis based on observation, personal experience, and data collection through generated questionnaire links shared with the target audience. The target audience is housewives, daily wage earners, working professionals, government employees, and businessmen, with a sample size of 160. The data analysis and measurement are based on Percentage Analysis, T-test, and ANOVA. JEL Classification Codes: G2, G4, G5, D1, M5, R3.